(untitled) (Research, Society and Development, 2021)
The filamentous fungus species Monascus produce natural pigments of different colors, in addition to bioactive compounds with antioxidant potential, being able to metabolize low cost substrates. However, there are several species of this genus that can exhibit different behaviors in relation to the production of pigments in the same production medium. Thus, the work proposal was to evaluate the behavior of two species of the genus Monascus, M. ruber URM 4530 and M. purpureus CCT 3802 regarding pigment production and, from the best results, evaluate the antioxidant activity of capturing ABTS+• radicals and DPPH• using cassava bran as a fermentative substrate and monosodium glutamate as a nitrogen source, with the aid of a Central Composite Design (DCC). As a result, better production and antioxidant activity were verified when using the M. purpureus strain, presenting 13.77 UA510 for the production of pigments and 96.1 % and 62.7 % inhibition of the radicals ABTS+• and DPPH•, respectively. In contrast, the M. ruber strain had a maximum production of 5.82 UA510. Thus, the results indicated different performances of the species of the genus Monascus, using the same residue as substrate and process conditions, with better pigment production performance and antioxidant activity for the strain M. purpureus CCT 3802.